GABA corelease guides the functional maturation of glycinergic synapses in an auditory sound localization circuit - Jongwon Lee; Brian Brockway; Karl Kandler (Proceedings of the National Academy of Sciences, 2026)
In the mammalian brainstem and spinal cord, glycine is the primary inhibitory neurotransmitter. However, during development, many glycinergic neurons also corelease the inhibitory neurotransmitter gamma-aminobutyric acid (GABA). Although the acute effects of GABA corelease on immature synaptic transmission have been increasingly characterized, its role in synapse maturation and circuit formation remains poorly understood. Here, we investigated the developmental roles of GABA corelease at glycinergic synapses from the medial nucleus of the trapezoid body (MNTB) to the lateral superior olive (LSO), an auditory pathway essential for binaural integration and sound localization. During the first two postnatal weeks, MNTB-LSO synapses corelease GABA and undergo pronounced synaptic and circuit refinement. Using conditional knockout mice with severely diminished GABA corelease from MNTB neurons, we found that key aspects of circuit refinement, including synaptic silencing and strengthening, occurred normally. However, a disruption of GABA corelease resulted in significantly larger quantal amplitudes and a reduced readily releasable vesicle pool, impairing the high fidelity and temporal precision of synaptic transmission, which are essential for accurate binaural processing. These results reveal a critical developmental role for GABA corelease in shaping the functional synaptic architecture of glycinergic synapses involved in sound localization.